Collaborative filmmaking as a conveyor of (migrant) women’s embodied experiences in Portuguese academia - Desille, A.; Azevedo, L.; Estevens, A.; Larrabure, S.; McGarrigle, J. (Ethnic and Racial Studies, 2026)
The collaborative film My place is in between places (2022) explores the experience of being a woman in contemporary Portuguese academia, bringing together researchers from diverse disciplines, career stages, and nationalities, united by a common experience of (past or present) migration. Drawing on multi-sensory feminist research methods and patchwork ethnography, we discovered that our voices resonate in unexpected interstices. Through this collaborative filmmaking process, we engage in collective reflection and made visible the embodied experiences of (migrant) women navigating in-between everyday spaces. This process deepens our understanding of migration, gendering dynamics, and the tension between precariousness and privilege in corporate academia. Collaborative filmmaking as a research method creates new social spaces of resistance and care. Furthermore, the act of writing and filming together generates complementary perspectives that converge into a polyphonic voice which can expand our understanding of subtle social issues. This approach fosters solidarity and support over competition.